2014
DOI: 10.1007/s11682-013-9287-3
|View full text |Cite
|
Sign up to set email alerts
|

Effects of acute psychosocial stress on neural activity to emotional and neutral faces in a face recognition memory paradigm

Abstract: Previous studies have shown that acute psychosocial stress impairs recognition of declarative memory and that emotional material is especially sensitive to this effect. Animal studies suggest a central role of the amygdala which modulates memory processes in hippocampus, prefrontal cortex and other brain areas. We used functional magnetic resonance imaging (fMRI) to investigate neural correlates of stress-induced modulation of emotional recognition memory in humans. Twenty-seven healthy, right-handed, non-smok… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
36
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 39 publications
(40 citation statements)
references
References 57 publications
4
36
0
Order By: Relevance
“…This is in line with previous findings demonstrating enhancement in emotion recognition on various emotional expressions (anger, disgust, fear, happiness, sadness, and surprise) in healthy participants as well as in patients with borderline personality disorder following the TSST (Deckers et al, 2015). However, some studies did not show enhancement in emotion recognition following exposure to acute stress (for example, Li et al, 2014). Future studies should pursue investigating the specific conditions under which the enhancement in emotion recognition takes place.…”
Section: Discussionsupporting
confidence: 89%
“…This is in line with previous findings demonstrating enhancement in emotion recognition on various emotional expressions (anger, disgust, fear, happiness, sadness, and surprise) in healthy participants as well as in patients with borderline personality disorder following the TSST (Deckers et al, 2015). However, some studies did not show enhancement in emotion recognition following exposure to acute stress (for example, Li et al, 2014). Future studies should pursue investigating the specific conditions under which the enhancement in emotion recognition takes place.…”
Section: Discussionsupporting
confidence: 89%
“…It is possible that anticipatory stress prior to entering the fMRI environment affects the ability of subjects to perform at an optimal level during an emotion challenge [48]. However, consistent with other studies [49], cortisol was not found to relate to task performance. Future investigations can more explicitly challenge specific emotions (i.e.…”
Section: Discussionmentioning
confidence: 53%
“…The extant research on stress and flexible affective control suggests two primary ways through which these impairments might occur. First, evidence suggests that stress exposure enhances affective responses and impairs emotional control when presented with stimuli such as emotional faces (17,18), negative images (19,20), and aversive stimuli (21)(22)(23). This suggests that stress could potentially enhance threat responses to the new CS+ that predicts shock, or prompt sustained threat responses to a newly safe cue, leading to a failure to extinguish threat responses to the new CSāˆ’ (24).…”
Section: Significancementioning
confidence: 99%